Clinical anatomy features of the buccal part of the facial vein. - E. V,, Blinova; Marina, Kapitonova; V. V,, Tatarkin; N. V., Mikutskaya; A., Khlebnikova; S. S, Dydykin (Clinical Dentistry LLC, 2023)
Abstract. Surgical interventions such as bishectomy or the oroantral fissure closure using the buccal extension of the buccal fat pad performed with transoral incision, which is associated with a significant number of risks. These risks include damaging of the facial vein and there is no information its relationships with the fat body of the cheek in literature. The aim of the study is to describe the features of the clinical anatomy of the buccal part of the facial vein and its relationships with the buccal extention of the buccal fat pad. Materials and methods. We used 30 fresh cadavers heads, 15 both males and females. Vessels been filled with silicone compound according to the M. Landofi method. Topographic and anatomical study was performed by layer-by-layer dissection on each side, so the total number of observations was 60. The relation of the facial vein to the facial artery, buccal fat pad and buccal muscle were described. Dissection results were photographed and recorded. Results. The facial vein was founded in 82% (n=49) cases. Were found 3 types of the relationship between the facial vein and the buccal fat pad. In the first type (58%; n=35), the facial vein passes through the buccal region between the outer surface of the buccal muscle and the buccal extension of the buccal fat pad. In the second type (15%; n=9), the facial vein lies on the surface of the buccal muscle anteriorly to the buccal fat pad. The third type (8%; n=5) — the facial vein lies superficially, outward from the buccal fat pad. In most cases the combined weight of 1 and 2 types of the facial vein relationships was 73% (n=44), the facial vein in the buccal region lies in the space between the buccal fat pad and the buccal muscle, crossing the most common horizontal incisions. Conclusions. The different types of the facial vein and buccal fat pad relationships should be taken into account as a potential risk factor during planning surgical interventions. Since in most cases the course of the facial vein crossing with the direction of the most common surgical incision, it is necessary to look for other safer options for surgical access to the buccal fat pad.